Comparison In Anaerobic Ability and Fatigue Indicator In Runners of 400m, 800m, and 1500m - Abdul Ghani, Ahmed; Morad, Hanan (Journal of Physical Education, 2017)
The research aimed at identifying the differences in anaerobic ability and fatigue indicator between 400m, 800m and 1500m runners. The research hypothesized significant differences between 400m, 800m and 1500m runners in anaerobic ability and fatigue indicator. The researcher used the descriptive method. The subjects were (8) 400m runners, (8) 800m runners, and (7) 1500m runners. Many tests were conducted the data was collected and treated using proper statistical operations. The researcher concluded that the decrease in anaerobic ability level with the increase of distance and running speed was more in 400m runners with great difference between 400m, 800m and 1500 runners. The rise in fatigue indicator along with distance and was more in 1500m runners. Finally the researchers recommended training adaptation in order for development to happen, developing anaerobic abilities for all middle distance runners for better achievements, making similar studies on other age groups and finally using precise tests for identifying the level of players and specifying their weaknesses.